Inadequate β-cell mass is essential for the pathogenesis of type 2 diabetes. Issue 3 (March 2020) - Weir, Gordon C; Gaglia, Jason; Bonner-Weir, Susan
Summary: For patients with type 1 diabetes, it is accepted among the scientific community that there is a marked reduction in β-cell mass; however, with type 2 diabetes, there is disagreement as to whether this reduction in mass occurs in every case. Some have argued that β-cell mass in some patients with type 2 diabetes is normal and that the cause of the hyperglycaemia in these patients is a functional abnormality of insulin secretion. In this Personal View, we argue that a deficient β-cell mass is essential for the development of type 2 diabetes. The main point is that there are enormous (≥10 fold) variations in insulin sensitivity and insulin secretion in the general population, with a very close correlation between these two factors for any individual. Although β-cell mass cannot be accurately measured in living patients, it is highly likely that it too is highly correlated with insulin sensitivity and secretion. Thus, our argument is that a person with type 2 diabetes can have a β-cell mass that is the same as a person without type 2 diabetes, but because they are insulin resistant, the mass is inadequate and responsible for their diabetes. Because the abnormal insulin secretion of diabetes is caused by dysglycaemia and can be largely reversed with glycaemic control, it is a less serious problem than the reduction in β-cell mass, which is far more difficult to restore.